School Choice Policies in the Political Spectacle - Linda Miller-Kahn; Mary Lee Smith (Arizona State University, 2001)
This article presents research on school choice. It takes the case of a school district in Boulder, Colorado, through the decade of the 1990s and shows how interest groups took advantage of federal, state, and district policies meant to promote school choice and molded them into a system of schools that met individualistic interests rather than the common good. Extensive interviewing and analysis of documents and media reports served as sources of evidence. The authors argue that district officials accommodated the demands of elite groups of parents to transform the district. The study is framed by revisionist theories of policy, particularly Murray Edelman's theory of political spectacle wherein real values are allocated to a few groups, the allocation occurring largely out of public scrutiny. For most of the public, however, policies are largely symbolic.